The effect of motivational interviewing-based intervention using self-determination theory on promotion of physical activity among women in reproductive age: A randomized clinical trial - Mahmoodabad, Seyed Saeed Mazloomy (Electron Physician, 2017)
BACKGROUND: Physical activity (PA) prevents chronic diseases. Self-determination theory (SDT) provides a useful framework to understand the nature of motivational interviewing (MI). OBJECTIVE: This study aimed to determine the effect of MI-based intervention using SDT on the promotion of PA among women in reproductive age. METHODS: Seventy women in reproductive age were selected by clustering sampling method for this randomized controlled trial. The questionnaire included the variables of physical fitness test, SDT, and global physical activity questionnaire (GPAQ). The validity of the questionnaires was approved using content validity ratio (CVR) and index (CVI). The reliability and internal consistency of the questionnaires and measures was approved using test-retest method and Cronbach’s alpha test, respectively. The intervention group (n=35) received four MI sessions through theory and one standard education session about PA. The control group (n=35) received a standard education session about PA. RESULTS: Four months after the intervention, an increase in the mean scores of total PA (p<0.001, ES=4.77), physical fitness tests including flexibility (p<0.001, ES=1.59), muscular endurance (p<0.001, ES=2.0), cardiorespiratory endurance (p<0.001, ES=0.51), and a decrease in mean scores of agility test (p<0.001, ES= − 0.51) and sedentary behavior (p<0.01, ES=− 0.74) was observed in the intervention group compared to the control group. The intervention group reported an increase in the scores of intrinsic motivation (p<0.001, ES=3.34), identified regulation (p<0.001, ES= 1.28), perceptions of competence (p<0.001, ES=0.81) and autonomy (p<0.001, ES=2.01), enjoyment (p<0.001, ES=0.98) and health motives (p<0.01, ES=0.19), health care climate (p<0.001, ES=4.6), and a decreased score of external regulation (p<0.01, ES=−0.55) and amotivation (p<0.01, ES= −0.56) over time, compared to the control group. CONCLUSION: MI-based intervention using SDT was effective on the promotion of PA. TRIAL REGISTRATION: The Trial was registered at the Iranian Registry of Clinical Trial (http://www.irct.ir) with the Irct ID: IRCT2015101924592N1.